Differences in Social Preferences - Are They Profitable for the Firm? - Hans-Ulrich Küpper; Kai Sandner (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2008)
This paper analyzes the impact of heterogeneous (social) preferences on the weighting and combination of performance measures as well as on a firm's profitability. We consider rivalry, egoism and altruism as extreme forms within the continuum of possible preferences and show that the principal can typically exploit both the altruistic and rivalistic behavior of his agents. Firm profits reach their maximum value if the agents are differentiated as much as possible in their individual characteristics. We provide further insight; namely, that in order to realize these gains in profitability, it is necessary to reallocate participation in performance measures such that competitive agents are privileged as compared to altruistic agents. In this context, stochastic interdependencies are of importance since they yield overlapping functions of the share parameters, causing additional adaptations in the optimal design of the wage compensation system.
urn:nbn:de:bvb:19-epub-2122-9
Keywords: D23; D82; D86; M41; M52; 650; Social Preferences; Rivalry; Altruism; Egoism; Team Composition; Performance Measurement